2018
DOI: 10.1097/spv.0000000000000579
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Repair of Pelvic Floor Disorders in Women Undergoing Surgery for Gynecologic Malignancies

Abstract: Using a large national surgical database, only 2.4% of women undergoing gynecologic cancer surgery had a concomitant POPUI procedure. Our data suggest that postoperative complications may not increase when concomitant surgery for POPUI is done at the time of gynecologic cancer surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…Furthermore, they found that these combination cases had a low but statistically significant increase in postoperative adverse events [8,9]. Previous studies have reported the incidence of major postoperative complications for combination urogynecologic and gynecologic cancer surgery has been found to be at a rate of 8.2%, which is similar to the major postoperative complication incidence rate of 9.8% in patients undergoing surgery for gynecologic cancers only [8,10].…”
Section: Introductionmentioning
confidence: 71%
“…Furthermore, they found that these combination cases had a low but statistically significant increase in postoperative adverse events [8,9]. Previous studies have reported the incidence of major postoperative complications for combination urogynecologic and gynecologic cancer surgery has been found to be at a rate of 8.2%, which is similar to the major postoperative complication incidence rate of 9.8% in patients undergoing surgery for gynecologic cancers only [8,10].…”
Section: Introductionmentioning
confidence: 71%
“…In the general female population, urinary incontinence problems affect approximately 30% (5–70%) [ 35 ], whereas 51–59% in patients before oncological treatment [ 17 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The treatment of reproductive organ statics abnormalities during oncologic treatment is not popular. An assessment of this issue is presented in the work of Bochenska et al [ 35 ], who studied 23,501 women treated for gynecologic cancers between 2010 and 2014. Data were obtained from available surgical registries of the American College of Surgeons National Surgical Quality Improvement Program.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many survivors of gynecologic malignancies have pelvic floor disorders and often have these symptoms before their oncologic treatment. Prior literature shows 53.1–59.5% 1,2 of women with gynecologic malignancies have stress urinary incontinence and 10.9% have symptomatic pelvic organ prolapse 3 . With a 20% lifetime risk of having pelvic floor reconstruction by the age of 80 years, there are many opportunities for surgical collaboration 4 .…”
mentioning
confidence: 99%